Clinical Evaluation of Medhyarasayana Ghrita along with Vachadi Ghrita Nasya (Pratimarsha) on Senile Dementia - Chaudhuri, K.; Samarakoon, S.M.S.; Chandola, H.M.; Kumar, R.; Ravishankar, B. (Indian Journal of Ancient Medicine and Yoga, 2010)
Mind and body are intimately associated with each other. The function of body organs depends on mental makeup of an individual and vice versa. Many factors such as stress, anxiety, depression, negative thoughts, unhealthy life style, unwholesome diet etc., influence mental and physical wellbeing. In senile Dementia progressive deterioration of memory, intellect, attention, thinking, comprehension and personality etc, is encountered during old age with preservation of normal level of consciousness. Medhyarasayana ghrita is a research based newly formulated medicine which contains sankhapushpi, mandukaparni, yastimadhu, guduchi, jyotishmati, kushmanda, ashwagandha, tulsi, bhallatak,kapikachchu and zinc processed with ghee. Vachadi ghrita in form of pratimarsha nasya was administered along with oral Medhyarasayana ghrita. Vachadi ghrita nasya contains vacha, kustha, pippali which also have rasayana property. On Hamilton Anxiety Rating Scale, patients had anxiety, tension, depression, difficulty in concentration & memory and fear. On Hamilton Depression Rating Scale, these patients had anxiety, depression, hypochondriasis and hopelessness. On Brief Psychiatry Rating Scale, psychological factors affected include anxiety, depression, somatic concern and tension etc. Medhyarasayana ghrita along with vachadi ghrita improved clinical features in statistically highly significant (p<0.001) manner. The bio-marker serum cholinesterase showed statistically insignificant improvement. The data reflects that disturbed mental health plays an important role in etiopathogenesis of senile dementia.